Quo Quadis Romanian Education? Brief Introspection - Vedinaş, Verginia; Godeanu, Teodor Narcis (Journal of Legal Studies, 2023)
This study aims to conduct a brief introspection of the current state of Romanian education, in general and of academic education, in particular. The approach is achieved under four coordinates: legislative evolution; a review of constitutional and legal provisions; a critical approach to academic education and possible solutions.